Peningkatan Pengetahuan Konselor Sebaya tentang Perilaku Seksual Remaja Melalui Pelatihan - Dien Gusta Anggraini Nursal; Aprianti Aprianti; Rachma Ridyanta (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
The purpose of this service was to provide youth counselor training about risky sexual behavior in Padang City State Senior High School in 2018. The method used in the pre and post experiment quasi. Pre Test was done to find out the students' initial knowledge about premarital sexual behavior. Then training was conducted on risky sexual behavior. After that the Post Test was carried out. Post Test was done to find out the results of the training of adolescent counselors about risky sexual behavior. The results of the knowledge analysis of students who took counseling on sexual behavior and peer counselors found that the average knowledge of students in the first survey before extension was 54.37 with a minimum value of 43.33 from a maximum of 66.67. Whereas in the second or post test measurement after giving the material obtained the average student knowledge about sexual behavior and peer counselor is 81.04 with a minimum value of 76.67 and a maximum of 86.67. So, there was a significant increase in knowledge in high school students in the independent pathway about sexual behavior and peer counselors.